JEJAK AWAL IMPERIUM INGGRIS DI ASIA: KANTOR DAGANG INGGRIS DI BANTEN 1602 – 1619 - Gregorius Andika Ariwibowo (LIPI Press, 2023)
Abstract The port of Banten in the early 17th century was widely known as a center for trading spices and other exoticproducts such as aromatic wood, cotton, and sugar. The presence of the British Merchants, which almost coincidedwith the beginning of the trade domination carried out by the Dutch Merchants, then led to a conflict between thetwo. This condition also influenced political stability in Banten, which had been fragile since the end of the 16thcentury. This study is a literature review from previous publications regarding the Sultanate of Banten in the early17th century. The literature discussed in this study mostly comes from compiled and written sources derived frommanuscripts and documentation of British traders regarding Banten in the early 17th century. Banten’s complexitiesas a cosmopolitan city that became a meeting place for foreign traders were limited to the exchange of cultureand knowledge and the arena of the struggle for power and trade hegemony. This is an intriguing series of eventsregarding the early traces of colonialism in Indonesia. The events led to the establishment of the City of Bataviaand the Dutch trading fleet’s dominance in the East Indies